Tinjauan Kritis Kerangka Kerja Pengkajian Filsafat Islam Pada Buku ‘History of Philosophy in Islam’ Karya T.J. De Boer: A Critical Review of the Study of Islamic Philosophy Framework's: An Analysis of the book History of Philosophy in Islam by Tjitze Jacobs de Boer - Ahmad Rizqi Fadlilah (Center of Islamic and Occidental Studies, 2023)
In the study of Islamic philosophy, De Boer is a representative figure and is considered his thought. His work entitled History of Philosophy in Islam is the first writing that is compiled holistically from the initial period of the formation of Islamic philosophy to the Medieval Period. This paper tries to read De Boer's thoughts in his work and critically analyze the framework he uses. This paper is qualitative in nature by taking the text as its data source, which is analyzed descriptively-critically with a philosophical and historical approach. In his work, De Boer chose